Identifying Sources of Imbalance in Individual Labour Markets - Meltz, Noah (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
The objective of this paper is to examine the operation of individual labour markets from the point of view of possible government intervention. The first section sets out a theoretical framework describing the operation of individual labour markets, while the second section develops a two-stage approach for identifying the sources of persistent imbalances in particular labour markets. The third section applies the proposed approach to three occupations in the Toronto area : auto mechanics ; sewing-machine operators ; and packaging hands. Alternative approaches by government are suggested for dealing with these imbalances.